Tuberculosis in the Bantu of Southern Rhodesia - Douglas Hoseason Shennan (Department of Medicine, 2024)
In many African territories tuberculosis is an increasing problem. southern Rhodesia is no exception to this rule . The great difficulty is the very ide front on ihich it needs to be faced; the claims of indust on the .African , overcrowding in tons, inadequate nutrition, lack of education and tribal breakdoin are all great proble s if taken separ tely, but to make an effective attack on tuberculosis they have to be dealt ith together. Tribal nomencl ture i very variable , and in the follo ing pages the conv~ntion has been used of puttin a capital letter at the beginning of the name , and again at the beginning of the stem; if the latter is not done the nae ·soften difficult to recognize. For instance , the Shangaa tribe may be 2 . referred to as AtnaShangana, or the Ngoni as ANgoni . In Part I, as ther are not many long tables, and those used are mainly of immedlate relevance , they have been included in the text instead of as an appendix. The tables for Part II are to be found in APpendix IV. The references are in the form: "(Hayres, 1951)", and are given in full , in alphabetical order, at the end. Places in southern Rhodesia and its neighbourhood referred to in the text have been included in the map.